Varying levels of historical nostalgia's effects on emotions - Marchegiani, Chris (School of Marketing, Curtin Business School, 2009)
This research examines changes in emotions of 292 respondents exposed to advertising and experiencing varying intensities of Historical Nostalgia. Five emotions related to Historical Nostalgia are examined under "low, mid, and high" intensity groups. In four of the emotions an increase in Historical Nostalgia significantly altered the level of emotions experienced, with the fifth a borderline result. This indicates the ability of Historical Nostalgia to effect emotions. Previous studies have empirically tested Historical Nostalgia independent from other forms of nostalgic appeal. As such, previous unknown knowledge as to how Historical Nostalgia at varying intensity levels influences respondent?s emotions is revealed.